Quality and Gravity in International Trade - Florian Unger; Lisandra Flach (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2017)
We show that the effect of fixed costs on international trade is lower in industries with a high degree of vertical product differentiation. We extend an international trade model by endogenous quality investmetns and use both aggregate trade data and firm-level data to estimate gravity equations of exports. Accounting for quality lowers the positive gains from trade and leads to more heterogeneous effects across industries compared to a trade model without quality.
Keywords: F12; F14; L11; 330